The impact of electronic management to build structural capital of banks in Algeria - A case study of the banks operating in setif- - Boufas, Achraf; Zouaoui, Khalissa (Milev Journal of Research and Studies, 2018)
The objective of this study is to determine the impact of emanagement on building the structural capital, which is the backbone of each organization, which is the whole organization after the departure of its employees, to a group of banks in Algeria. This study should be dropped on the applied side of the banks under study. In order to achieve the objectives of the study and analysis of the collected data, using sppss22 program. The study reached a set of results and made recommendations to the banks' supervisors.